2021
DOI: 10.3390/nu13030868
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Cognitive Functions in Sports: A Systematic Review and Meta-Analysis

Abstract: Cognitive functions are essential in any form of exercise. Recently, interest has mounted in addressing the relationship between caffeine intake and cognitive performance during sports practice. This review examines this relationship through a structured search of the databases Medline/PubMed and Web of Science for relevant articles published in English from August 1999 to March 2020. The study followed PRISMA guidelines. Inclusion criteria were defined according to the PICOS model. The identified records repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 65 publications
2
43
0
Order By: Relevance
“…However, more power during lifting and sprinting was produced in male athletes than in female athletes. Beyond the physical aspect, it was found that a low or moderate dose of caffeine can improve self-reported energy, mood, and cognitive functions such as attention in sports practice [ 32 ]. These reports show that caffeine administration may be an important factor in competitive performance at an elite level where results depend on narrow margins and may also be helpful for amateurs in beating their personal records.…”
Section: Ed Ingredients—caffeine and Taurine Contributionmentioning
confidence: 99%
“…However, more power during lifting and sprinting was produced in male athletes than in female athletes. Beyond the physical aspect, it was found that a low or moderate dose of caffeine can improve self-reported energy, mood, and cognitive functions such as attention in sports practice [ 32 ]. These reports show that caffeine administration may be an important factor in competitive performance at an elite level where results depend on narrow margins and may also be helpful for amateurs in beating their personal records.…”
Section: Ed Ingredients—caffeine and Taurine Contributionmentioning
confidence: 99%
“…Carbohydrate (CHO) and caffeine (CAF) ingestion are supported by strong evidence to have beneficial effects on exercise and cognitive performance and used by professional and/or highly trained athletes to increase training and match performance [ 1 3 ]. CAF binds to adenosine receptors A 1 and A 2 , reducing the influence of the parasympathetic system and increasing the synthesis of neurotransmitters such as dopamine and catecholamines, increasing cognitive performance [ 4 ], tension, vigor and perception of vitality and a reduction between training load and ratings of perceived exertion (RPE) on elite and moderately trained athletes [ 5 ]. At the peripheral level, CAF improves sodium-potassium (Na + -K + ) pump activity and increases the bioavailability of calcium (Ca 2+ ) in the myoplasm [ 6 ]; mechanisms that explain an enhancement of one repetition maximum (1-RM) [ 7 ] power output with a determined load [ 8 ] and muscular endurance [ 9 ] in resistance exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive functions include a lot of basic mental operations, such as attention, memory, and executive functions involving working memory, decision-making, and multitasking (Lorenzo Calvo et al, 2021 ). Among these functions, attention is the one mainly defined as allocating cognitive resources to internal or external stimuli, which is key for sports performance (Furley and Wood, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The participants in the control group listened to an audio-book segment on natural history, which was 15 mins long, and the results indicated that a brief mindfulness intervention could decrease the negative influence s of MF on basketball freethrows. Kabat-Zinn described mindfulness as "paying attention in a particular way, on purpose, in the present moment, and nonjudgmentally" (Sierpina, 2005) 2021) states that the intake of caffeine could improve attention (Lorenzo Calvo et al, 2021). Listening to self-selected music would be a suitable method of reducing MF in endurance performances (Lam and Phillips, 2019).…”
Section: Tactical Performancementioning
confidence: 99%